Evolution of S‐cysteinylated and S‐glutathionylated thiol precursors during grape ripening of Vitis vinifera L. cvs Grechetto, Malvasia del Lazio and Sauvignon Blanc. (7th July 2015) - Cerreti, M.; Esti, M.; Benucci, I.; Liburdi, K.; de Simone, C.; Ferranti, P.
Abstract Background and Aims Varietal thiols, important odorous molecules in wine, have been identified in Vitis vinifera L. grapes as S‐cysteinylated and S‐glutathionylated odourless precursors. The aim of this paper is to investigate the presence of these precursor compounds during ripening of two Italian white grape cultivars, Grechetto and Malvasia del Lazio, in comparison with the well‐characterised, reference cultivar Sauvignon Blanc. Methods and Results Grapes were sampled and sorted according to density in order to obtain homogeneous samples at the TSS concentration of 16, 19 and 22°Brix, as a synthetic index of ripening stage. After sorting and processing the grapes, the concentration of thiol precursors contained in each sample of juice was determined by liquid chromatography‐quadrupole MS. For the first time, S‐3‐(4‐sulfanyl‐4‐methylpentan‐2‐ol)‐glutathione was identified and quantified in the three cultivars as a glutathione‐conjugated precursor. Both S‐cysteinylated and S‐glutathionylated precursors were ubiquitous in the three cultivars, although their concentration varied significantly. Conclusion Thiol precursors increased with TSS during ripening in Sauvignon Blanc and Grechetto, while no variation of these odourless compounds was observed in Malvasia del Lazio, which also had a lower concentration of these precursors. Significance of the Study This work contributes to defining the significance of these precursors to the varietal attributes of the resulting wines, as well as indicating the optimal harvest time of grapes for maximal expression of thiol varietal attributes in wine.